Design and simulation of a combined serpentine t-shape magnetorheological brake - Faishal Harish Hidayatullah; Ubaidillah Ubaidillah; Endra Dwi Purnomo; Dominicus Danardono Dwi Prija Tjahjana; Ilham Bagus Wiranto (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
A magnetorheological brake (MRB) is a device to dissipate rotational energy using magnetorheological fluids (MRF). MRB can change its braking torque quickly in response to external magnetic field strength. The brake is rotational, utilizing the MRF in shear mode. In this study, the geometrical design of the MRB, magnetic circuit and MRF flow path is addressed. Mathematical models are presented that describe the braking torque of the MRB. A novel prototype is introduced combining T-shape rotor model with serpentine flux magnetic circuit configuration. The rotor member is selected to direct the flux concentration at that location. Serpentine flux configuration is selected to achieve higher torque without increasing the size of MRB by activated more surface area of MRF with the magnetic flux. The finite element method is used to evaluate the magnetic flux density in MRB using FEMM 4.2. FEMM results showed that this novel design could provide sufficient magnetic flux along MRF flow path. Finally, the influence of input current to the MRB on braking torque is investigated. It is found that the braking torque in MRB increases with the increase of the input current. The prototype is formulated as foot-drop prevention orthotic. The MRB would be further integrated into ankle-foot orthoses for post-stroke patients. The design is formulated as a preliminary geometrical design, aiming to obtain the minimum required braking torque.